JURNALISME BENCANA DALAM PEMBERITAAN BENCANA BANJIR DI KABUPATEN LOMBOK BARAT TAHUN 2021 : (Analisis Wacana Kritis pada Situs Lombokpos.jawapos.com) - Ummu Salamah; Hartin Nur Khusnia; Muhlis (Jurnal Ilmiah Mahasiswa Komunikasi (JIMaKom), 2023)
ABSTRACT This study aims to determine the discourse of flood reporting in West Lombok Regency in 2021 on the Lombokpos.jawapos.com website from the perspective of disaster journalism. This research uses a qualitative descriptive method based on the critical discourse analysis put forwards by the Teun A. van Dijk model, which has three dimensions of analysis, including text analysis, social cognition and social context. The research data collected were news reports about the flood disaster in West Lombok in 2021 derived from the local media site lombokpos.jawapos.com. The results of this study revealed that in the text dimension, the construction of flood disaster news discourse in the pre-disaster phase focused on conveying disaster mitigation programs implemented by the government. In the disaster response phase, the discourse construction mostly contains reporting on the conditions and needs of the community at the disaster site as well as aid distribution activities. Whereas in the post-disaster phase, news discourse construction focuses on monitoring the rehabilitation and reconstruction process, such as recovery programs by the government and related parties. Keywords: Disaster journalism, Critical discourse analysis, Floods